Investigating the use of Large Language Models in software security requirements: Results of a literature review - Melo, Amália; Almeida, Lucas; Garcés, Lina (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE); 2025: Anais do IV Workshop Brasileiro de Engenharia de Software InteligenteDO - 10.5753/ise.2025.14892, 2025)
This study investigates the application of Large Language Models (LLMs) in the context of security requirements engineering through the conduction of a rapid literature review. The review enabled the characterization of current research in this domain with respect to: (i) the purposes for which LLMs are employed in security requirements activities; (ii) the families of LLMs explored (e.g., GPT, BERT, LLaMA), their capabilities (e.g., classification, generation), and underlying architectures (e.g., encoder, decoder, encoder-decoder); (iii) the techniques adopted for conditioning or guiding LLM behavior; (iv) the datasets used to train, fine-tune, or validate these models; and (v) the evaluation metrics applied to assess the performance of LLMs in supporting security requirements tasks. The findings contribute to a structured understanding of the current state of research and highlight key trends, gaps, and opportunities for advancing the use of LLMs in secure software engineering.